Understanding Factors Influence E-Commerce Use Behavior in Indonesia - Yevis Oesman, Daduk Mansur, Ernie Sule, Dwi Kartini, (Opción, 2019)
This study proposes a model as a tool to predict consumer behavior of e-commerce in Indonesia with the personal user as a unit analysis. Results show that Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), Habit (H), Perceive Risk (PR), Perceive Convenience (PC), Trust (T) positive influence to Behavior Intention (BI). Only Facilitating Conditions (FC) not gives positive influence to BI. The Unified Model of Use Behavior become a fit model to predict e-commerce adoption with R2 result 0.85. In conclusion, the operator should improve the marketing strategy with refer to this research.